Em busca do popular no discurso de lula: significação, transcodificação e semiose - Oliveira, Maria Lúcia de (2007)
This study aims to analyze the Lula's speech, seeking reveal the socio-cultural values ​​that explain its popularity. We used the greimasian semiotics as a basic theoretical model, especially that sóciossemiótica takes care of non-literary texts social. Investigated a corpus composed of four manifested discourses that portray different times of Lula's political career: President Lula syndicalist early stage denouncing the business class; Squid Congressman it is critical that the maintenance of indirect elections president; Lula and the letter to the Brazilian is the speech that redefines his political career President Lula of Brazil, speech after the first victory at the polls. The speeches were analyzed following the trajectory of the generative course of meaning in the underlying popular search. On the narrative level, we investigated the relationship between the semiotic subjects and their valuables. In the discursive level, there were the interpersonal relations of enunciation and utterance and spatiotemporal projections and key highlight was the ideology underlying the speeches. Studies have shown that semas democracy, citizenship and ethics, implicit in the texts analyzed, have a number of restrictions, including considerations are that: only worker is honest, the poor must live in hope and that maintaining "Storylines" enthusiasts is the solution to the problems that crucify the country. The analysis and comparison of the four texts also showed that the popular arguments are tactical procedures used masterfully in speeches as the intentions of the producers in order to produce a discourse of domination that seems include dominated in decision-making. In fact, they tend to further strengthen domination. This allows us to say that political actors appeal to the doctrines sentimentalists oriented abstract conceit, subordinating reason to feeling.